Analysis of the Need for Canva-Based Electronic Modules to Improve Vocational Learning Outcomes - Ade Holisoh; Henny Setiani; Hendi Firdaus; Lukman Nulhakim; Yayat Ruhiat (Jurnal Penelitian Pendidikan IPA, 2023)
The goal of education is not just to increase one's head knowledge, but also one's skill set, outlook, and frame of mind. Learning results are affected by the quantity and quality of reading resources available in schools. "e-module" refers to an electronic media-based educational tool. Teachers and students alike can benefit from the enhanced imagination that comes from using Canva media. Descriptive qualitative research was used to investigate these issues; in both the literature review and the field research, the researchers provided precise and detailed descriptions of their observations and findings. The researchers here are concerned with the importance of manufacturing things, and their subjects are teachers in vocational high schools (SMK). Teachers have expressed a desire for electronic modules that serve as learning medium for teaching vocational subjects. Students who need learning media other than textbooks to transfer material to vocational high school students benefit from the usage of e-modules because they increase their understanding and learning efficiency both in school and at home. Students require learning materials that are accessible and engaging. One of these resources is an engaging electronic module with homework questions designed to aid in students' character development and moral upbringing